Contributions of rhodopsin, cone opsins, and melanopsin to postreceptoral pathways inferred from natural image statistics - Barrionuevo, Pablo Alejandro (2014)
Visual neural representation is constrained by the statistical properties of the environment. Prior analysis of cone pigment excitations for natural images revealed three principal components corresponding to the major retinogeniculate pathways identified by anatomical and physiological studies in primates. Here, principal component analyses were conducted on the excitations of rhodopsin, cone opsins, and melanopsin for nine hyperspectral images under 21 natural illuminants. The results suggested that rhodopsin and melanopsin may contribute to the three major retinogeniculate pathways. Rhodopsin and melanopsin may provide additional constraints in natural scene statistics, leading to new components that cannot be revealed by analysis based on cone opsin excitations only.